Analytic approach for dependency relationship between data and organisational goals - Tengku Adil Tengku Izhar; Torab Torabi; M. Ishaq Bhatti (The International Journal of Management Science and Information Technology (IJMSIT), 2017)
This paper proposes an approach to utilise information from operational data to support the organization goal. The challenge in this issue is how to convert this vast of data into useful information. This is critical for all enterprises to remain competitive. In this paper, we emphasized the dependency relationship involve between the variables such as organization goal, sub-goals, actions, data input and data output. This relationship is important to assist the development of data measurement, data analysis and data modelling. Simple algorithm is developed to support the relationship between the variables. The paper presents an evaluation using the case study.
Keywords: 650; Analytic; Data; Organisational Goals; Sub-Goals